Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ar.24481
|View full text |Cite
|
Sign up to set email alerts
|

Xanthoangelol alleviates cerebral ischemia reperfusion injury in rats

Abstract: Ischemia/reperfusion (I/R) injury accounts to be a prime cause of neurological deficit following stroke. This study aimed to explore the neuro‐protective effects of Xanthoangelol (XAG) on I/R‐induced injury in both in vivo and in vitro models. Our data demonstrated that XAG can shrink infarct size and brain edema in middle cerebral artery occlusion (MCAO) model. In addition, XAG was capable of alleviating the neurological deficit in rats that have undergone MCAO procedure. Meanwhile, antiapoptotic activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Besides, xanthoangelol plays a role as an anticancer (Yang et al, 2019) and antibacterial agent (Inamori et al, 1991). Recently, in vivo and in vitro studies performed by Chao et al (2020) found that xanthoangelol could attenuate cerebral I/R injury by mitigating apoptosis through the remission of oxidative stress concomitant with Nrf2 activation (Chao et al, 2020).…”
Section: Effect Of Natural Chalcones On Different Types Of I/r Injurymentioning
confidence: 99%
“…Besides, xanthoangelol plays a role as an anticancer (Yang et al, 2019) and antibacterial agent (Inamori et al, 1991). Recently, in vivo and in vitro studies performed by Chao et al (2020) found that xanthoangelol could attenuate cerebral I/R injury by mitigating apoptosis through the remission of oxidative stress concomitant with Nrf2 activation (Chao et al, 2020).…”
Section: Effect Of Natural Chalcones On Different Types Of I/r Injurymentioning
confidence: 99%
“…And researchers discovered that activating Nrf2 was the critical mechanism [ 70 ]. Xanthoangelol is an important ingredient of propolis, which triggered Nrf2 to treat ischemic stroke [ 71 ].…”
Section: Flavonoidmentioning
confidence: 99%
“…Prenylated chalcones have drawn increased attention in the fields of nutrition and cancer prevention because of their pharmacological effects, which have been thoroughly studied in vitro and in preclinical investigations [ 12 ]. Xanol is known to have protective effects against allergic diabetes, inflammation, infection, ischemia, neurodegeneration, muscle loss, oxidative stress, tumor growth, and tumor metastasis [ 6 , 7 , 13 , 14 ]. However, the pharmacological and molecular effects of xanol on OSCC have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%